Public participation in environmental governance initiatives of chemical industrial parks. (10th July 2021) - Wang, Yuanni; Zhang, Ruilian; Worden, Sandy; Cao, Hailin; Li, Chunhua
Abstract: A chemical industrial park is a socioeconomic and ecological composite system formed by the interaction of multiple stakeholders, such as chemical companies, the government, and the public. The environmental governance of chemical industrial parks requires the participation of multiple parties. However, when considering the environmental problems of chemical industrial parks, researchers mainly investigate such problems based on the parks or the government, and there is a lack of research from the perspective of multiple subjects. In this paper, we take public participation in China's chemical industrial parks as an example and, based on semi-structured interviews and questionnaires, analyse the current situation of public participation in the environmental governance of chemical industrial parks. We find that public participation is characterized by a situation of "helplessness". This helplessness has three causes: (1) a weak foundation for public participation, (2) limited public participation channels and (3) ineffective CIP management committees. We also discuss changes required at the government level, fostering public participation in environmental governance of chemical industrial parks and implications for theory and practice on cleaner production.